Development Interactive Vending Machine For Supporting The Health Protocol of The New Normal Era at Telkom University - Kurniawan, Ady Purna; Utoro, Rio Korio; Siradj, Yahdi; Akhara, Amnaduny (School of Applied Science, Telkom University, 2024)
Telkom University through the Covid19 task force team urges all employees to comply with health protocols while in the campus environment. Facilities such as masks, hand sanitizers, temperature scanners, and gate sterilizers have been provided to protect the campus community. The entire campus community is encouraged to isolate if there are symptoms of a Covid-19 virus attack. This Vending Machine was developed to provide health protocol facilities in the campus environment with the support of interactive multimedia technology. The development of this tool uses the Prototyping method which focuses on the main functions. The result of the Vending Machine development is that transactions can be used through the Android mobile application device directly through the desktop application contained on the screen at the Vending Machine. The results of the Vending Machine test state that 100% of the functions run according to the procedure and the device User Interface gets a value of 76.9 from the System Usability Scale test method.